CFD simulation of air to air enthalpy heat exchanger: Variable membrane moisture resistance - Al-Waked, R. (Elsevier Ltd, 2015)
Conjugate heat and mass transfer processes across membrane heat exchangers of variable mass transportation resistance were investigated numerically. One half of flow channel for the hot stream and another for the adjacent cold stream were simulated. Effects of channel height, Reynolds number and flow direction on heat exchanger thermal effectiveness and energy recovered were studied. The validated CFD model showed that values of moisture resistance decrease with the increase in flow rates and/or the decrease in vapour mass fractions on both sides of the membrane. Furthermore, total hydraulic diameter effects on the thermal efficiency within membrane heat exchangers were found strong. Â© 2015 Elsevier Ltd.